Turkish Germans in the Federal Republic of Germany : immigration, space, and belonging, 1961-1990 - Thomsen Vierra, Sarah 1979- (Publications of the German Historical Institute, 2018)
"As the largest national group of guest workers in Germany, the Turks became a visible presence in local neighbourhoods and schools and had diverse social, cultural, and religious needs. Focussing on West Berlin, Sarah Thomsen Vierra explores the history of Turkish immigrants and their children from the early days of their participation in the post-war guest worker program to the formation of multi-generational communities"--